Dynamic adaptability of services by integrating service oriented architecture and enterprise architecture : doktorski rad - Ramljak, Darije (D. Ramljak ; Fakultet elektrotehnike i računarstva, 2018)
Effective discovery of services and their usage in environments that change dynamically is very cumbersome. In addition, technology today is a business innovation enabler, and there needs to be a way to link customer experience and business concepts such as products and value offers to service technology design. In this thesis we have introduced and elaborated a new Service Oriented Business Ecosystem Architecture method and a model to enable service description design using business level information focusing on variation elements, derived after applicability analysis, from relevant Enterprise Architecture (EA) and Service Oriented Architecture (SOA) artefacts and concepts. We have elaborated our new approach through the example of an ecosystem as a good representation of a complex environment in which enterprises have to offer their services and operate and focus on finding a good formalized structure that enables creation of a model and a method for defining service descriptions that can be used later in dynamic selection and binding. The thesis research and work resulted in creation of a comprehensive method and a model framework with multiple levels of abstraction with developed tool support for dynamic transformation of business information and related artefacts. In our research we have analyzed EA and SOA methods and principles to define informational elements for conveying business capabilities and intents towards service property descriptions and further down to realization elements. Elaboration of meta-model and model creation as a process of conveying variability related informational elements from the business layer towards the technology oriented layers were given, as well as elaboration of service exposure levels and transformation business rules associated with service litmus tests and a notion of potential future extension elements were outlined. The demonstration of innovative elements was two-fold. First during creation of the meta-model and underlying toolset, and second by using the method and tools in a case study with an ecosystem combining electronic public sector services with commercial financial service providers and startups. Finally, an evaluation was provided comparing the current service and model adaptation experience and overall improvements of the meta-modeling approach including the tool development process elaboration. Keywords: service design, business modeling, service modeling, capabilities, SOA, EA